Detecção de indícios de depressão em textos curtos usando transferência de conhecimento - Lima, Guilherme Matheus de Aguiar (Brasil, 2023)
During the 2020 COVID-19 pandemic, cases of people living with depression increased significantly. This fact combined with the low detection rate of the disease in initial reception and with the increasing use of social network users to express their feelings characterized social networks as a favorable place for the early detection of manifestations of depression. With that in mind, this work proposes a model for detecting posts related to the topic of depression on Reddit and a second model that uses the Reddit model as a feature extractor on Twitter.